3
$\begingroup$

For a circle homeomorphism $f: S^1 \rightarrow S^1$ we can define the the rotation number $$ \rho(f) = \lim_{n \rightarrow \infty} \frac{1}{n}(F^n(x) - x) \mod 1, $$ for a lift $F:\mathbb{R} \rightarrow \mathbb{R}$ of $f$ and a point $x \in \mathbb{R}$. $\rho(f)$ exists always and is independent of $x$ and $F$. In this wikipedia article it says that the rotation number is invariant under topological semi-conjugacy, i.e. for two homeomorphisms $f,g$ of the circle the rotation numbers $\rho(f) = \rho(g)$ are equal if there is a continuous, surjective and monotone map $h:S^1 \rightarrow S^1$ with $$ f \circ h = h \circ g. $$ I proof why this is true for homeomorphisms $h$ can be found here in chapter 11. I don't understand why this is still true if $h$ is no homeomorphism.

Thanks

$\endgroup$
3
$\begingroup$

The following argument is an extension of the one for a homeomorphism $h$ in [Hasselblatt & Katok. A First Course in Dynamics. Cambridge University Press, 2003, pg. 128].

We will show (for the right choice of $G$), $\frac{|F^n(x) - G^n(x)|}{n} \to 0$ as $n \to \infty$ for all $x$, where $F$ and $G$ are lifts of $f$ and $g$ respectively, i.e. $\pi F = f \pi$, where $\pi: \mathbb{R} \to \mathbb{S}^1$ is the projection operator.

Let $H$ be a lift of $h$. Then $\pi F H = f \pi H = f h \pi= h g \pi = h \pi G = \pi H G$. This implies $F \circ H = H \circ G + k$ for some $k \in \mathbb{Z}$. Another lift $G'$ of $g$ may be chosen so that $F \circ H = H \circ G'$. In particular, let $G'(x) = G(x) + k$. Since $H$ is a degree-one lift, $H(x + k) = H(x) + k$ for any integer $k$. Then $H \circ G'(x) = H (G(x) + k) = H(G(x)) + k = F \circ H(x)$.

For the rest of the argument, assume the lift $G$ is chosen so that $F \circ H = H \circ G$.

By induction $F^n\circ H = H \circ G^n$: this holds true for $n = 1$ and assuming $F^{n-1} \circ H = H \circ G^{n-1}$ then

$\begin{aligned} F^n\circ H &= F^{n-1}\circ F \circ H\\ &= F^{n-1} \circ H \circ G\\ &= H \circ G^{n-1} \circ G\\ &= H \circ G^n \end{aligned}$.

This implies $G$ may be chosen so that $F^n\circ H = H \circ G^n$, where $H$ is any lift of $h$.

Suppose $H$ is the lift such that $H(0) \in [0,1)$. Then for all $x \in [0,1)$, since $0 < H(0) \leq H(x) < H(1) = H(0) + 1 < 2$, we have $ -1 \leq H(x) -x \leq 2$ for all $x \in [0,1)$. Since $H$ is a degree-one lift, $H(x) - x$ is periodic with period $1$, so this implies for all $x \in \mathbb{R}$, $|H(x) - x| < 2$.

Thus, $|H\circ G^n(x) - G^n(x)| < 2$.

Using the fact $F^n(x + 1) = F^n(x) + 1$ for all $x$, we have $F^n(x + 2) = F^n(x) +2$, and $F^n(x-2) = F^n(x) - 2$. Suppose $| y - x | < 2$, so $ x - 2 < y < x + 2$. Since $F^n$ is strictly increasing, $F^n(x-2) < F^n(y) < F^n(x + 2)$, hence $F(x) - 2 < F^n(y) < F^n(x) + 2$. Therefore, if $|y-x| < 2$, we have $|F^n(y) - F^n(x)| < 2$.

Since $|x - H(x)| < 2$, we have $|F^n(x) - F^n\circ H(x)| < 2$.

Therefore,

$\begin{aligned} |F^n(x) - G^n(x)| & = |F^n(x) - F^n\circ H(x) + F^n\circ H(x) - G^n(x)|\\ &= |F^n(x) - F^n\circ H(x) + H\circ G^n(x) - G^n(x)|\\ &\leq |F^n(x) - F^n\circ H(x)| + |H\circ G^n(x) - G^n(x)|\\ &< 2 + 2 \end{aligned}$

Hence, $\frac{|F^n(x) - G^n(x)|}{n} < \frac{4}{n} \to 0$ as $n \to \infty$.

This implies $\rho(f) = \rho(g)$.

$\endgroup$
  • $\begingroup$ Nice answer, but I have a litter puzzle, why $F$ is strictly increasing? $\endgroup$ – Hu xiyu Dec 4 '17 at 7:01
  • $\begingroup$ How do you guarantee that $H$ is a degree-one map? Since $h$ is not bijective this is not true anymore. $\endgroup$ – ghreis Apr 2 '18 at 16:11

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.